1971
DOI: 10.1113/jphysiol.1971.sp009546
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine secretion by the adrenal medulla of the foetal and new‐born foal

Abstract: SUMMARY1. The content and output of adrenaline and noradrenaline from the equine adrenal medulla has been investigated under different conditions in foetuses, foals and adult mares.2. In the foetus only small amounts of both amines were secreted in response to stimulation of the peripheral ends of the splanchnic nerves to the gland; during anoxia the adrenal discharge was far greater and was independent of any nervous mechanism.3. Whereas in the ruminant a direct adrenal response to low Po2 is confined to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0
1

Year Published

1974
1974
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 17 publications
4
38
0
1
Order By: Relevance
“…It has also been shown that the innervation of the adrenals is not fully functional until late gestation in these two species (Comline & Silver, 1961, 1966, which would coincide with the apparent increase in adrenocortical sensitivity to ACTH. Events in the foal are also consistent with this hypothesis since the adrenal cortex is unresponsive to ACTH and the innervation of the gland is incomplete until very close to term (Comline & Silver, 1971;. No corresponding information on the development of the splanchnic innervation is as yet available for the fetal pig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has also been shown that the innervation of the adrenals is not fully functional until late gestation in these two species (Comline & Silver, 1961, 1966, which would coincide with the apparent increase in adrenocortical sensitivity to ACTH. Events in the foal are also consistent with this hypothesis since the adrenal cortex is unresponsive to ACTH and the innervation of the gland is incomplete until very close to term (Comline & Silver, 1971;. No corresponding information on the development of the splanchnic innervation is as yet available for the fetal pig.…”
Section: Discussionsupporting
confidence: 62%
“…In the present study, a rise in fetal plasma cortisol was observed in response to ACTH released (Lohse & First, 1981). In the foal the main adrenal growth spurt occurs at or even after birth (Comline & Silver, 1971 (Taylor, 1987), the hysterotomy and search for suitable vessels for sampling probably caused some disturbance to placental flow and led to ACTH release. The fetal pituitary is certainly competent from about 0-65 gestation in the lamb and responds to stress with raised ACTH output (Alexander, Britton, Forsling, Nixon & Ratcliffe, 1974).…”
Section: Discussionmentioning
confidence: 77%
“…However, group 2 foals showed a significant cortisol response to ACTH, whereas group 1 animals did not despite rising ACTH levels 90-120 min after insulin administration. Adrenocortical sensitivity to endogenous ACTH therefore appears to increase towards term in the fetal foal as is known to occur in response to exogenous ACTH Silver & Fowden, 1994 (Comline & Silver, 1971). The enhanced noradrenaline response to hypoglycaemia observed in group 2, in the present study, may therefore be due, in part, to maturation of the innervation to the fetal adrenal medulla.…”
Section: Discussionsupporting
confidence: 57%
“…In the newborn, insulin-induced hypoglycaemia leads to a dramatic rise in plasma adrenaline with little, if any, change in plasma noradrenaline (Silver et al 1987). Adrenaline is present in the adrenal medulla of the fetal foal during late gestation and can be released in response to asphyxia and direct nerve stimulation under acute conditions in utero (Comline & Silver, 1971). Moreover, the enzyme phenylethanolamine-N-methyl transferase, which converts noradrenaline to adrenaline, is detectable in the fetal adrenal medulla from 250 days of gestation and shows no change in abundance between then and the immediate postnatal period (Han, Fowden, Silver, Holdstock, McGladdery, Ousey, Allen, Rossdale & Challis, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation